Slow freezing should not be totally substituted by vitrification when applied to day 3 embryo cryopreservation: an analysis of 5613 frozen cycles - Zhu, Hai-Yan (J Assist Reprod Genet, 2015)
PURPOSE: This study aimed to compare slow freezing (SF) and vitrification (VT) techniques for day 3 embryo cryopreservation in infertile couples. METHODS: This retrospective cohort study enrolled 5613 infertile patients, with 7862 frozen-thawed day 3 embryos and 3845 vitrified-warmed day 3 embryos, from 2010 to 2014, at a single center. The rates of embryo survival, pregnancy, implantation, miscarriage, live birth, and live birth weight were compared between the two groups. RESULTS: A total of 5613 cycles with 5520 transfers were analyzed. Using SF, the rates of overall embryo survival and fully intact blastomeres were lower than those in VT (91.5 vs. 97.4 % and 68.7 vs. 92.3 %, respectively). The rate of good quality embryos after thawing/warming was lower in SF than in VT. In single frozen embryo transfer cycles (FETs), the pregnancy and implantation rates were similar between the two groups (35.0 vs. 40.8 % and 34.6 vs. 35.9 %, respectively). In double FETs, the pregnancy rate per cycle was also similar between the groups (58.8 vs. 58.4 %). The implantation rate per embryo transfer was significantly higher with SF than with VT (38.8 vs. 34.6 %). With adjustment for maternal age and the number of good quality embryos, differences in implantation rate remained significant (adjusted P value, SF vs. VT P < 0.05). No independent effect was found for the method of cryopreservation on the pregnancy rate. No significant differences in the rates of miscarriage, live birth, and live birth weight were observed between the two techniques. CONCLUSIONS: Despite the significantly low embryo survival rate, fully intact blastomere rate, and good quality embryo rate in SF, the pregnancy and implantation rates were not adversely affected in single and double FETs. SF yielded an equivalent miscarriage rate, live birth rate, and live birth weight compared with VT. The SF protocol to cryopreserve day 3 embryos still should be considered.